2018
DOI: 10.3390/en11040901
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Nonlinear Dynamic Evaporator Model in Supercritical Organic Rankine Cycle Waste Heat Recovery Systems

Abstract: The organic Rankine cycle (ORC)-based waste heat recovery (WHR) system operating under a supercritical condition has a higher potential of thermal efficiency and work output than a traditional subcritical cycle. However, the operation of supercritical cycles is more challenging due to the high pressure in the system and transient behavior of waste heat sources from industrial and automotive engines that affect the performance of the system and the evaporator, which is the most crucial component of the ORC. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In other respects, as a result of the calculations made for simple ORC in the previous paper, the net power production, thermal and exergetic efficiencies are calculated as 79.23 kW, 15.51% and 27.20% for the subcritical ORC and 81.52 kW, 15.93% and 27.76% for the Different types of ORC configurations (simple, regenerative, subcritical or supercritical) has many advantageous and disadvantageous to each other. For instance, the investment cost of a supercritical ORC is higher than that of a subcritical one [12,68] Moreover, compared with the subcritical ORC, the supercritical ORC has a higher turbine inlet pressure which affects the safety as well as investment cost [69,70]. When the ORC systems are compared in term of the regenerative and simple (non-regenerative) cycle, there are many studies which prove the superiority of the performance of rORC over simple ORC [71][72][73][74][75][76].…”
Section: Effect Of the Regeneratormentioning
confidence: 99%
“…In other respects, as a result of the calculations made for simple ORC in the previous paper, the net power production, thermal and exergetic efficiencies are calculated as 79.23 kW, 15.51% and 27.20% for the subcritical ORC and 81.52 kW, 15.93% and 27.76% for the Different types of ORC configurations (simple, regenerative, subcritical or supercritical) has many advantageous and disadvantageous to each other. For instance, the investment cost of a supercritical ORC is higher than that of a subcritical one [12,68] Moreover, compared with the subcritical ORC, the supercritical ORC has a higher turbine inlet pressure which affects the safety as well as investment cost [69,70]. When the ORC systems are compared in term of the regenerative and simple (non-regenerative) cycle, there are many studies which prove the superiority of the performance of rORC over simple ORC [71][72][73][74][75][76].…”
Section: Effect Of the Regeneratormentioning
confidence: 99%
“…The results shown that the R1234ze had a better performance than any other organic fluids. Chowdhury [12] carried out the dynamic performance of ORC using a finite volume method. They concluded the proposed model could capture transient effects of more than 90% of data fitness.…”
Section: Literaure Reviewmentioning
confidence: 99%
“…This method is robust and has a higher accuracy than other conventional methods such as zone modelling method. However, the method is extremely time consuming for simulation and cannot be used in real time control applications [7,22]. A novel model of the evaporator using fuzzy logic technique is therefore developed in this paper.…”
Section: Evaporator Modelmentioning
confidence: 99%
“…The numbers of the membership functions were selected in a way so that they are adequate to represent the nonlinearity of the evaporator and can achieve at least 90% accuracy against the reference FV based evaporator model in [21]. The range of the membership functions and their design can be found in detail in [22].…”
Section: Fuzzy Based Dynamic Evaporator Modelmentioning
confidence: 99%
See 1 more Smart Citation